3-Phenyl-3H-naphtho[1,2-e][1,2,3]oxadiazine - Alia D. Aouant; George Varvounis (Molbank, 2022)
In this study, we considered the reaction of (E)-1-[(2-phenylhydrazono)methyl]naphthalen-2-ol with iodobenzene diacetate in dichloromethane-produced novel 3-phenyl-3H-naphtho[1,2-e][1,2,3]oxadiazine in 11% yield. By analogy to previously published work, we suggested that the reaction proceeds via the intermediacy of an o-naphthoquinone azomethide that undergoes conjugated 6π-electrocylization to produce the product. 1D, 2D NMR, HRMS, IR, and UV-VIS spectra provided information that supported the structure of the product.